Memperkukuh keselamatan negara abad ke-21: Peranan Polis Republik Indonesia ke atas keamanan dan ketenteraman / Muhammad Alwafi - Muhammad , Alwafi (2016)
Indonesian National Police (POLRI) has a strategic role and occupies an important position in determining Indonesia’s national security. This thesis generally seeks to analyze the aspects that strengthen national security in the 21st century. Given the extent of the scope of the national security, specifically the research is intended to describes the history of the development of POLRI, analyzes the implementation of Grand Strategy POLRI 2005 – 2012, and reviews various efforts to revitalize the role of POLRI in maintaining peace and order. To pursue the research objectives, this thesis applies qualitative methodologies. In addition, seven prominent and intellectual figures who have the authority and expertise in the field of police and national security were interviewed. The results of the study suggest that the POLRI has primary responsibility for maintaining domestic security and ensuring the security and peace of society. Specifically in terms of peace, there were five threats that could disrupt the stability and security; they were cybercrime, narcotics, terrorism, radicalism and anarchism. The POLRI should enhance its role in meeting the growing threats of good quality as well as quantity. In this context, the POLRI claimed to raise the professionalism and develop a new paradigm of civilian police. Structural reforms, instrumental and cultural should be accompanied by corresponding with the real implementation of POLRI duties in the society field. However, revitalizing and optimizing of the future role of POLRI should refer to the three main orientations of the principles of democracy, rule of law and human rights.